Case report: A case of giant malignant solitary fibrous tumor of the pleura with Doege-Potter’s syndrome and review of the literature - Li, Jie; Tang, Hong-Tao; Liu, Qing; Li, Cai-Han; Chen, Wei-Yang; Yu, Zeng-Wei; Wang, Lei; Lin, Lin; Zhao, Jin-Lan; Zhao, Chun-Yan; Chen, Long-Qi; Tian, Dong (Frontiers in Oncology, 2024)
The solitary fibrous tumor of the pleura (SFTP) is a rare intrathoracic neoplasm that commonly originates from the subpleural mesenchymal cells of the visceral pleura and accounts for less than 5% of all pleural tumors. We reported a case of a 54-year-old man with a two-week history of hypoglycemia, a six-month history of productive cough and fatigue, and chronic right chest pain. Radiological techniques revealed a giant intra-thoracic mass with hypervascularization, and pathological staining was carried out to make a definitive diagnosis of SFTP. Interventional embolization was conducted to block the main feeding vessels before the surgery, and an anterolateral thoracotomy combined with a transverse sternotomy was performed to achieve a complete resection, which demonstrates significant potential for further application in patients with unilateral giant SFTP. The postoperative course was uneventful, with no signs of hypoglycemia observed during the follow-up. Additionally, we reviewed and prospected the research progress on SFTP. The aim of this study is to enhance clinicians’ understanding of SFTP through our case and to provide a detailed review of the current research.